Association Between Internet Addiction and the Risk of Musculoskeletal Pain in Chinese College Freshmen – A Cross-Sectional Study - Yang, Guang; Cao, Jianhua; Li, Yingke; Cheng, Peng; Liu, Bin; Hao, Zongji; Yao, Hui; Shi, Dongzhe; Peng, Li; Guo, Liya; Ren, Zhongyu (Frontiers in Psychology, 2019)
Background: It is well established that greater internet use is related to an increased risk of musculoskeletal pain among adolescents. The relationship between internet addiction, a unique condition involving severe internet overuse, and musculoskeletal pain has, however, not been reported. The aim of this study was to examine the association between internet addiction and the risk of musculoskeletal pain in different body parts among Chinese college freshmen. Methods: A cross-sectional study was conducted among 4211 Chinese college freshmen. Internet addiction status was evaluated using the 20-item Young's Internet Addiction Test. Internet addiction was defined as internet addiction score ≥ 50. Musculoskeletal pain was assessed using a self-report questionnaire. Results: Among all subjects, 29.2% reported neck pain, 33.9% shoulder pain, 3.8% elbow pain, 7.9% wrist/hand pain, and 27.9% low back and waist pain. The prevalence of internet addiction was 17.4%. After adjusting for potential confounders, internet addiction was significantly associated with risk of neck, shoulder, elbow, wrist/hand, low back and waist pain. The odds ratios and 95% confidence intervals (CI) for neck pain with severe internet addiction status were 1.00 (reference), 1.451 (1.221, 1.725), and 1.994 (1.608, 2.473) (P for trends: <0.001). The odds ratios (95% CI) for shoulder pain with severe internet addiction status were 1.00 (reference), 1.520 (1.287, 1.795), and 2.057 (1.664, 2.542) (P for trends: <0.001). The odds ratios (95% CI) for elbow pain with severe internet addiction were 1.00 (reference), 1.627 (1.016, 2.605), and 2.341 (1.382, 3.968) (P for trends: 0.001). The odds ratios (95% CI) for wrist/hand pain with severe internet addiction status were 1.00 (reference), 1.508 (1.104, 2.060), and 2.236 (1.561, 3.202) (P for trends: <0.001). The odds ratios (95% CI) for low back and waist pain with severe internet addiction status were 1.00 (reference), 1.635 (1.368, 1.955), and 2.261 (1.813, 2.819) (P for trends: <0.001). Conclusion: This cross-sectional study showed that severe internet addiction is significantly associated with a higher risk of musculoskeletal pain in Chinese college freshmen. In future research, it will be necessary to explore causality in this relationship with interventional studies.